Accelerated aging tests to selective solar absorber coatings for low temperature applications - Diamantino, Teresa (2022)
ABSTRACT: The need of a higher role of solar energy within the energy mix in the coming decades obliges the collectors to increase their performance and reliability. It is demanded that the solar absorbers, as the key component of solar thermal collectors, should be low cost with high efficiency for extended lifetimes under different kinds of environments. Commercially, there are presently two main types of solutions as selective solar absorbers coatings for low temperature applications: coatings obtained by physical vapour deposition (PVD) and by paint coatings (PC). These coatings present different physical and chemical characteristics. Therefore, it is important to know how these commercial coatings degrade over time in different environments. Results obtained with two different PVD coatings and three PC, under different accelerated aging tests, are presented. The aging tests performed included different environmental stress corrosion conditions: temperature, humidity, chlorides, sulfur dioxide and nitrogen oxides. The chlorides and the gases SO2 and NO2 affect distinctly the different selective coatings. Cyclic variation of corrosion promoting gases (sulfur dioxide and nitrogen dioxide), higher humidity, salt spraying and drying seem to be an aging test that reflects the different environments where the solar thermal collectors are exposed. In addition to the contaminants, drying/wetting cycles also play an important role in degradation mechanisms of absorber coatings. So, the international standard ISO 22975-3 needs to be revised to include cyclic conditions with these contaminants.